GERCEP: Gerakan Cek Kesehatan dan Cegah Sedari Dini, Kolaborasi KKN UNS untuk Meningkatkan Kesadaran Kesehatan Masyarakat di Desa Dibal, Kabupaten Boyolali - Amalia, Gita; Andreas Rony Wijaya; Afni Arifatul Hidayah; Al Khansa; Arnella Hayya Amalia Ovin; Bernadeta Chrisma Damai Saputri; Eva Purnama Sari; Neti Kurnia Sari; Nur Setyo Jatiningtyas; Tegar Adji Syahputra; Widya Putri Haryati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The GERCEP Program: The Health Check and Early Prevention Movement The Community Service Program (KKN) team from Sebelas Maret University implemented this program in Dibal Village, Boyolali, as a preventive measure against the still-high prevalence of non-communicable diseases and stunting. Activities included free health checkups, stunting prevention education, and nutrition label reading training, all of which used a participatory approach. The program successfully engaged 104 residents in health checkups, 23 Posyandu mothers in stunting prevention education, and 31 Posyandu cadres in nutrition literacy training. Results showed an increase in community knowledge and awareness of the importance of early detection, as well as improved health worker skills in understanding nutrition information. These results confirm the effectiveness of community-based health interventions in promoting healthy lifestyles and supporting the achievement of Sustainable Development Goals 2 and 3.